2009
DOI: 10.1056/nejmoa0906612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of the Initial Cases of 2009 Pandemic Influenza A (H1N1) Virus Infection in China

Abstract: Surveillance of the 2009 H1N1 virus in China shows that the majority of those infected have a mild illness. The typical period during which the virus can be detected with the use of real-time RT-PCR is 6 days (whether or not fever is present). The duration of infection may be shortened if oseltamivir is administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

71
438
17
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 530 publications
(532 citation statements)
references
References 10 publications
71
438
17
6
Order By: Relevance
“…In our present study, the shedding of 2009 H1N1 virus was assessed in 173 patients: after 5 days of oseltamivir treatment, 88 patients (50·8%) still had a positive RT‐PCR result. These results agree with those of recent studies that found that patients admitted to hospital with the pandemic influenza 2009 H1N1 virus had a longer duration of viral shedding than adults who were hospitalized with a seasonal influenza virus infection 12, 13, 14…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our present study, the shedding of 2009 H1N1 virus was assessed in 173 patients: after 5 days of oseltamivir treatment, 88 patients (50·8%) still had a positive RT‐PCR result. These results agree with those of recent studies that found that patients admitted to hospital with the pandemic influenza 2009 H1N1 virus had a longer duration of viral shedding than adults who were hospitalized with a seasonal influenza virus infection 12, 13, 14…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those of previous studies 13, 18. A recent Italian study19 has reported that the duration of viral shedding is significantly reduced when therapy is initiated within 2 days of symptom onset.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As has been previously reported, gastrointestinal symptoms are prominent and suggesting for the pandemic H1N1 2009 influenza infection 1 , 2 , 3 . In the present study, clinical manifestations of the pandemic H1N1 2009 influenza virus infection are similar to the report from China, 1 but different from U.S. and U.K reports. In addition, there are both positive and negative clinical predictors for pandemic H1N1 2009 influenza infection.…”
Section: Discussionsupporting
confidence: 81%